Pedagogical and professional competences policies in improving education - Suzanti, Erma; Sugiyarto, Sugiyarto; Nurulmatinni, Nurulmatinni (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
The purpose of this study is to test the influence pedagogical and professional competence in improving a quality education. This research is a correlational quantitative. The paper used questionnaire as instrument. The result showed that pedagogical and professional competence together influence the quality of education. The paper recommends to more concern on pedagogical and professional competence where the school would have good quality education.